Chemical Composition and Antioxidant Activity of Ganoderma lingzhi and Ganoderma lucidum Fruiting Body Extracts - H. I. Harbatsevich; L. S. Zenevich; I. R. Batalova; S. A. Kovalenko; P. M. Bychkovsky (Регуляторные исследования и экспертиза лекарственных средств, 2024)
INTRODUCTION. Ganoderma spp. have been used as a traditional oriental medicine and a bioactive dietary supplement. These fungi are a promising source of effective antioxidants. Currently, there is no regulatory framework to control the quality of this herbal drug and its bioactive components in the Russian Federation and the Republic of Belarus. Therefore, it is essential to study the chemical composition and pharmacological activity spectrum of G. lingzhi and G. lucidum extracts.AIM. The aim of this study was to determine the chemical composition and antioxidant activity of G. lingzhi and G. lucidum fruiting body extracts.MATERIALS AND METHODS. The study focused on pure cultures of G. lingzhi and G. lucidum obtained from the fungal species collection of the Forest Institute of the National Academy of Sciences of Belarus. Fungal biomass was grown using two substrates, including alder sawdust (1–3 mm fraction) and oak shavings (5–10 mm fraction). The fungal biomass was extracted using repeated maceration with 70% ethanol. The study tested the free radical-scavenging activity of the extracts in reactions with the stable free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) and the radical cation derived from 2,2’-azinobis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS). The chemical composition was analysed by high-performance liquid chromatography–mass spectrometry (HPLC–MS). The assays for phenols, steroids, and triterpenes used spectrophotometry.RESULTS. The extract of G. lucidum strain 334 cultivated on the alder substrate demonstrated the highest free radical-scavenging activity (IC50=3.1±0.2 μg/mL (DPPH), IC50=3.7±0.2 μg/mL (ABTS)), the highest phenolic content (326.2±16.5 µmol/g), and the highest triterpene content (2.00±0.11 mmol/g) of all the studied extracts. The antioxidant activity of the extracts of G. lingzhi and G. lucidum may be attributed to the content of ganoderic acid D, lucidenic acid D, naringenin, and other phenolic compounds.CONCLUSION. The high yield of extracts with a significant radical-scavenging activity makes artificially cultivated G. lingzhi and G. lucidum mushrooms a promising source of natural antioxidants.